The Importance of Using Checklist in Measuring the Comprehensiveness of English Teaching Materials: A Systematic Literature Review - Basaruddin, Muhammad Azwan; Mustafa, Hema Rosheny (Asian Journal of Assessment in Teaching and Learning, 2023)
The aim of this paper was to provide evidence pertaining to the practice of using checklists in analysing the comprehensiveness level of the English teaching materials prepared to be used during the teaching and learning process. A systematic literature review (SLR) of empirical studies exploring the practices of using checklists in analysing the English teaching materials was performed. A total of 12 papers were included in the SLR. It was discovered that the use of a checklist in analysing teaching materials could highlight the differences in teachers’ perceptions; promote convenient methods to keep record; identify the strengths and weaknesses of the materials; encourage systematic method of analysis; offer flexibility for current changes; lead to adaptation of the existing materials. It is also suggested in the future, bigger-scale research should be conducted and repeating analysis using the similar checklist could be done in order to improve the accuracy in obtaining the data.